(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Objective: to increase the effectiveness of treatment of chronic recurrent aphthous stomatitis of the oral mucosa against the background of chronic gastroduodenitis by correcting dysbiotic disorders and enhancing antioxidant protection through pathogenetic therapy. Methods: general clinical, laboratory, biochemical, functional, instrumental and statistical methods were used in the course of the study. Results obtained: Clinical studies in patients with chronic recurrent aphthous stomatitis of the oral mucosa against the background of chronic gastroduodenitis have shown: a decrease in the following indicators by 1.24 times, a deterioration in hygiene by 1.92 times, an increase in the Schiller-Pisarev test by 2.06 times, an increase in stimulated salivation by 1.84 times and the absence of stimulated salivation by 2.09 times, a shift in The pH is in the acidic side. Conclusions: The results of clinical and laboratory studies during operative and long-term follow-up showed that the therapeutic and prophylactic complex developed by us for the treatment of oral mucosal diseases in chronic gastroduodenitis has a long-term bactericidal effect against pathological microbes. The local immune status of the oral cavity was observed to approach the norm.